Determinants Factors Affecting Stunting In Children 2-5 Years In The Working Area Of Tajinan Public Health Center - Maulina, Rifzul (Faculty of Medicine and Health Science, Universitas Islam Negeri Maulana Malik Ibrahim, 2020)
Background: Malang Regency is included in the 100 priority districts for stunting with a stunting rate of 20% spread over 6 priority villages.Objective: The research was to analyze risk factors related to child, mother, and environmental factors for stunting under five years old.Method : The study used a case-control design population was all children aged 2 to 5 years at the Tajinan Public Health Center for six months in 2018. The case sample was 75 stunting toddlers and the control was 75 toddlers well-nourished. Data was collected by interview and measurement (anthropometry). Data was analyzed by chi square test and multiple logistic regression.Result : 80% of stunted children had infectious diseases, a history of length of birth 48 centimeters and low birth weight was 72% and 10%, a history of breastfeeding and complementary foods (59%). The risk factors for stunting were a history of low birth weight, a history of infectious diseases, maternal education, environment sanitation, and family income.Conclusion : The most influential factors are history of infectious diseases and environment sanitation. It is necessary to increase family empowerment related to the prevention of infectious diseases through improving dietary and health care patterns and improving environment sanitation.